2021
DOI: 10.1155/2021/7571132
|View full text |Cite
|
Sign up to set email alerts
|

Glycyrrhiza Genus: Enlightening Phytochemical Components for Pharmacological and Health‐Promoting Abilities

Abstract: The Glycyrrhiza genus, generally well-known as licorice, is broadly used for food and medicinal purposes around the globe. The genus encompasses a rich pool of bioactive molecules including triterpene saponins (e.g., glycyrrhizin) and flavonoids (e.g., liquiritigenin, liquiritin). This genus is being increasingly exploited for its biological effects such as antioxidant, antibacterial, antifungal, anti-inflammatory, antiproliferative, and cytotoxic activities. The species Glycyrrhiza glabra L. and the compound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 190 publications
(170 reference statements)
1
37
0
2
Order By: Relevance
“…LCA, recognized as a chalcone extracted from Glycyrrhiza, possesses anti-cancer abilities. Our previous study reported that LCA derived from Glycyrrhiza could restrain cell viability, induce cell cycle arrest and apoptosis, and elevate the cellular ROS levels in HepG2 (8). The underlying mechanism of the anticancer activities of LCA remains elusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LCA, recognized as a chalcone extracted from Glycyrrhiza, possesses anti-cancer abilities. Our previous study reported that LCA derived from Glycyrrhiza could restrain cell viability, induce cell cycle arrest and apoptosis, and elevate the cellular ROS levels in HepG2 (8). The underlying mechanism of the anticancer activities of LCA remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…The sweetness of Glycyrrhiza makes it widely used as a confectionary and condiments. It also contains various nutrition, such as saponins and chalcones, which enabled it to display antioxidant, antiproliferative, anti-inflammation, and immunoregulatory activities (8). It contains diverse phytochemicals such as saponins and chalcones.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of chemical substances, including 126 small molecules and 6 polysaccharides, have been isolated from Scutellaria baicalensis, mainly belonging to the categories of flavonoids and glycosides [11]. Glycyrrhiza uralensis encompases bioactive molecules, such as triterpene saponins and flavonoids [12]. Concerning Ziziphus jujuba Mill, 22 compounds were identified in the ethanol extract.…”
Section: Phy906mentioning
confidence: 99%
“…Its name derives from the Greek words ‘glykos’ that means sweet and ‘rhiza’ that means root ( Sharma et al, 2018 ). The genus Glycyrrhiza comprises more than 30 species that are extensively dispersed worldwide mainly at Mediterranean regions of Asia ( Sharifi-Rad et al, 2021 ). This plant has been documented and reviewed as traditional remedy for the prevention of painful swellings, cough, colds, and influenza.…”
Section: Introductionmentioning
confidence: 99%
“…G. glabra and its bioactive phytochemicals holds multiple pharmacological activities like, antidemulcent, expectorant, antiulcer, anti-inflammatory, anticancer and antidiabetic as an evidence from various review held in recent past ( Pandey et al, 2017 ; Sharma et al, 2018 ). Wider utility in traditional medicinal system and proven scientific validated studies makes liquorice and its bioactive compounds ( Figure 1 ) as drug of choice to explore it more precisely for multiple health benefit possibilities as an evidence from many published studies reviewed in past ( Revers, 1956 ; Ren and Wang, 1988 ; Olukoga and Donaldson, 2000 ; Saxena, 2005 ; Asl and Hosseinzadeh, 2008 ; Kaur et al, 2013 ; Kao et al, 2014 ; Hosseinzadeh and Nassiri-Asl, 2015 ; Yang et al, 2015 ; Dastagir and Rizvi, 2016 ; Pastorino et al, 2018 ; Sharma et al, 2018 ; Bredin, 2019 ; Mamedov and Egamberdieva, 2019 ; Batiha et al, 2020 ; Chen et al, 2020a ; Jiang et al, 2020 ; Kwon et al, 2020 ; Rehman et al, 2020 ; Wang et al, 2020 ; Hasan et al, 2021 ; Sharifi-Rad et al, 2021 ). Further, utility through novel drug delivery specially nanomedicine approaches, cosmeceutical application and as an animal feed alternative are well discussed and reviewed recently ( Alagawany et al, 2019 ; Ciganovic et al, 2019 ; Rani et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%